1987
DOI: 10.1093/clinchem/33.8.1349
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of direct bilirubin by use of bilirubin oxidase.

Abstract: We developed an enzymatic method for measuring direct-reacting bilirubin (DBIL) in serum. At pH 4.5, bilirubin oxidase (BOX) oxidizes mono-conjugated bilirubin, di-conjugated bilirubin, and most of the delta-bilirubin to biliverdin. The resulting decrease in absorbance at 460 nm is linearly related to the concentration of DBIL in serum. Mean DBIL values in the 51 patients' sera examined by the BOX method and a diazo procedure (Clin Chem 1982;28:2305) were 45.4 and 42.8 mg/L, respectively. For the same samples,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Bile samples were diluted 1:1000 with 50% methanol, and then fluorescence was determined at 380 nm excitation and 430 nm emission wavelengths for BaP-type metabolites using a PerkinElmer (Model LS50B, MA) luminescence spectrometer with the slit width set at 2.5 nm. Generally, BaP metabolites are normalized to the protein level (Lin et al, 1996) or to biliverdin (absorbance at 380 nm) (Doumas et al, 1987), but increased variance has been reported by some (Aas et al, 2000;Richardson et al, 2004;Vuorinen et al, 2006). As we also saw greater variance with normalized data (data not shown), we used non-normalized data.…”
Section: Bap Metabolite Measurement In Bilementioning
confidence: 99%
“…Bile samples were diluted 1:1000 with 50% methanol, and then fluorescence was determined at 380 nm excitation and 430 nm emission wavelengths for BaP-type metabolites using a PerkinElmer (Model LS50B, MA) luminescence spectrometer with the slit width set at 2.5 nm. Generally, BaP metabolites are normalized to the protein level (Lin et al, 1996) or to biliverdin (absorbance at 380 nm) (Doumas et al, 1987), but increased variance has been reported by some (Aas et al, 2000;Richardson et al, 2004;Vuorinen et al, 2006). As we also saw greater variance with normalized data (data not shown), we used non-normalized data.…”
Section: Bap Metabolite Measurement In Bilementioning
confidence: 99%
“…Direct spectrophotometry, using bilirubinometers, as well as diazotization methods are the two most common and popular assays for measuring serum bilirubin levels [17]. Total bilirubin levels, as measured using a diazotization method, vary with the concentration and type of the diazo reagent [18], the pH of the reaction mixture [19], and the duration of the reaction [20], but are not affected by the presence of lipemia [16]. Before the lipemia-simulation experiment, all blood specimens should be measured for the level of total bilirubin with a diazotization method to obtain a standard reference, and this reference should be similar to levels of total bilirubin, measured with the spectrometry method in the absence of lipid (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Before lipemia simulation test, all samples were first analyzed for total bilirubin using the diazotization method (Roche/Hitachi cobas c501 analyzer), which is not affected by lipemia [16], to provide reference for baseline data.…”
Section: Methodsmentioning
confidence: 99%
“…Direct spectrophotometry is not affected by the variables associated with diazo assays, but it is available only to those who possess a certain type of instrumentation. 17,18…”
Section: Sampling Of Veinsmentioning
confidence: 99%